ENDOSCOPIC FINDINGS AND TREATMENT OUTCOME IN CASES PRESENTING WITH DYSPHAGIA - Hafeez, Muhammad; Salamat, Amjad; Saeed, Farrukh; Zafar, Hafiz; Hassan, Fayyaz; Farooq, Asif (Journal of Ayub Medical College Abbottabad, 2011)
Background: Dysphagia results from impeded transport of liquids, solids, or both from the pharynx to the stomach. Among the malignant lesions, carcinoma of oesophagus is the commonest cause. Our objective was to find out the frequency of different endoscopic lesions and outcome of the endoscopic therapeutic interventions in patients presenting with dysphagia. Methods: This descriptive study was conducted at Department of Gastroenterology, Military Hospital Rawalpindi from June 2008 to May 2009. Patients of dysphagia after their consent were interviewed about the symptoms. Relevant biochemical investigations were done. Barium swallow and upper Gastrointestinal (GI) Endoscopy were carried out. Benign strictures were dilated with Savary Gilliard Dilators. Malignant strictures were further evaluated to decide treatment plan. In patients considered to have oesophageal dysmotility, pressure manometery was done before specific therapy. Results: Seventy nine patients were enrolled. Twenty-five had malignant strictures, out of those commonest was adenocarcinoma 14 (56%). Twentynine had benign strictures the commonest being Gastro-oesophageal Reflux Disease (GERD) related peptic stricture 9 (31%). Fifteen had oesophageal dysmotility, and achalasia was present in 10 out of them. After evaluation 12 out of 25 patients with malignant strictures were considered fit for surgery. Self-expanding metal stents (SEMS) were passed in 5. All benign strictures were dilated with SavaryGillard dilators. Pneumatic balloon dilation was done in patients of achalasia. Conclusion: The commonest malignant lesion resulting in dysphagia was adenocarcinoma while in benign it was GERD related peptic stricture. Achalasia was most frequent in oesophageal motility disorders. Standard of treatment for early oesophageal malignancy is surgical resection. SEMS is a reliable way to allay dysphagia in inoperable cases. Savary Gillard dilatation in benign, and pneumatic balloon achalasia dilatations are effective ways of treatment. Keywords: Dysphagia, Malignant strictures, Benign strictures, Motility disorders, Achalasia